Normative Legal Analysis of Notary Code of Ethics: Improving Legal Professional Ethical Standards - Prasetyo, Wakhid (Institute Of computer Science (IOCS), 2024)
The notary profession plays a critical role in a country's legal system, requiring notaries to adhere to the highest ethical standards to maintain integrity, professionalism, and public trust. This research aims to analyze the gap between the existing notary code of ethics and the expected ethical standards. Using a normative legal approach, the study examines primary legal materials, including statutory regulations, ethical guidelines, and relevant court decisions, as well as secondary legal sources. The research findings reveal several gaps between the current notary code of ethics and the anticipated ethical standards. One significant gap is the lack of firm regulations addressing potential conflicts of interest that may arise in notarial practice. Additionally, the study identified differences in the enforcement of ethical sanctions and complaint mechanisms for code of ethics violations. These findings underscore the importance of strengthening the notary code of ethics to ensure alignment with the profession's expected ethical standards. By addressing these gaps, the notary profession can further enhance its integrity, professionalism, and the public's trust in the legal system. The study's insights can inform policymakers and regulatory bodies in their efforts to refine and reinforce the ethical framework governing the notary profession